ANALISIS MOTIVASI KERJA KARYAWAN KOPERASI PEGAWAI NEGERI UNIVERSITAS TANJUNGPURA PONTIANAK - Claudia, Cristina; Okianna, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the intrinsic and extrinsic work motivation that has been carried out by employees of the civil servant cooperative in Tanjun Peninsula pontianak. the research method used is descriptive in the form of qualitative research. Data collection tools used in the form of check lists, interview guidelines, and documentation. From the results of the study, it is known that the type of intrinsic motivation that influences the performance of employees of the pomtianak tanjupura university civil servant cooperative based on its most dominant level of importance is responsibility, the second job itself, the third progress to develop, the fourth award and the fifth achievement. and the types of extrinsic motivation that affect the performance of employees of the pontianak tanjupura university civil servant cooperative, based on the most dominant level of importance is the basis of salary payments, the second is interpersonal relations, the third is working conditions, the fourth is cooperative administration and policy, and the fifth supervision. Keywords: Work Motivation, Employees of Pontianak Untan District.